Heritage Language Dilemma: Generational Attitudes and Cultural Identity Among Tamil Diaspora in Indonesia - Simanjuntak, Ivan Fernando; Br. Perangin-angin, Alemina; Rusdi Noor Rosa (Indonesian Journal of Advanced Research, 2024)
This study examines heritage language maintenance, cultural identity formation, and language attitudes within the Tamil community in Medan, Indonesia. Employing ethnolinguistic identity theory and family language policy perspectives, it investigates factors influencing Tamil language transmission and its impact on ethnic identity. Surveys of 10 Tamil families reveal significant generational differences in attitudes towards Tamil maintenance. While 85% of parents view it as crucial for cultural preservation, only 50% of children share this sentiment, prioritizing societal assimilation. Both groups recognize the value of bilingualism and the cultural disconnection stemming from limited Tamil proficiency. Challenges including discrimination, insufficient community support, and inadequate resources hinder intergenerational language transmission. This study offers unique insights into the complex dynamics shaping heritage language maintenance in diasporic communities, highlighting the need for targeted interventions to support linguistic and cultural continuity.